GENTRIFICAÇÃO E POLÍTICAS DE REVITALIZAÇÃO NOS CENTROS HISTÓRICOS NO BRASIL: processos que levam ao déficit habitacional - Georgia Patrícia da Silva (Universidade Federal do Maranhão, 2008)
This article is a critical discussion about policies to preserve the Brazilians ́ historic centers which need to protect local and cultural groups, but in practice, are in the process of gentrification? that increases housing problems for those entering the consuming culture areas. The process of gentrification ? linked to business interests inevitably makes the local residents leave their areas considered inherited by them, to create power landscapes to motivate commercial exploitation. This creates new centralities that provide higher returns towards investments made.